Padang State University of Public Nutrition Services Center (Promotion, Quality of Resources, Quantity of Facilities) - Elsa Yuniarti; Pudia M Indika; Prima Minerva; Reza Febrianto Nurdin; Randi Kurniawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The main objective of the PPUPIK program at the community nutrition service center is toencourage Padang State University clinics to provide holistic community nutrition services. Theimplementation of this activity is managed by a group of lecturers who scientifically have a closerelationship with the program to be created. It is hoped that the proposal for a community nutritionservice center will develop well in providing individual and community services based on clinicalnutrition. Community nutrition service centers are oriented towards other health service efforts found inclinics, namely promotive, preventive, curative and rehabilitative. The advantage of this service centercompared to other first-level health facilities such as the puskesmas is that the services provided areaccompanied in the field when carrying out counseling and provision as an integrity service. The maintargets of community nutrition services are children, adolescents, pregnant women and the elderly. Theprograms carried out include nutrition service programs for infants and toddlers, nutrition services foradolescents, nutrition services for pregnant women, nutrition services for the elderly and preparticipation examinations.